Pengembangan LKPD Geometri Berbasis Etnomatematika Tari Kejei - Lambayu, Putri Ewis; Masri, Masri; Asmara, Adi; Jumri, Rahmat; Ristontowi, Ristontowi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to Develop geometry teaching materials based on the ethnomathematics of the Kejei Dance that are valid and practical for use in mathematics learning. This research employs the Research and Development (R&D) method with a 4D Development model consisting of the define, Design, Develop, and disseminate stages. However, this study is limited to the Develop stage. The subjects of this study were 22 seventh-grade students of SMPN 09 Lebong. The data collection instruments used were expert validation sheets to measure the validity of the teaching materials and questionnaires for teachers’ and students’ responses to determine the practicality of the product. The results show that the geometry teaching materials based on the ethnomathematics of the Kejei Dance obtained an average validity score of 87.3%, categorized as very valid based on expert assessments of material and media. In addition, the practicality test results based on teachers’ and students’ responses showed an average percentage of 91.7%, categorized as very practical. These results indicate that the Developed teaching materials are feasible for use in mathematics learning. Kata Kunci: Teaching Materials, Ethnomathematics, Geometry, Kejei Dance, Student Worksheets.